NCRAD Family Study and NIA‐LOAD brain tissue: A NCRAD resource. (1st February 2022) - Nudelman, Kelly N. H.; Oblak, Adrian L; Faber, Kelley M.; Reyes‐Dumeyer, Dolly; Issen, Heather; Lacy, Kaci; Wilmes, Kristi; Marshall, Jeanine D.; Case, K. Rose; Mitchell, Colleen M.; Hobbick, Chris C.; Mayeux, Richard; et al.
Abstract: Background: Brain tissue is an invaluable resource for researchers investigating the pathological etiology and molecular basis of Alzheimer's disease (AD), but this resource is scarce and difficult to obtain compared to other types of biospecimens. The National Centralized Repository for Alzheimer's Disease and Related Dementias (NCRAD) stores and distributes brain tissue to researchers to address this research gap. Method: NCRAD stores fresh frozen, formalin fixed brain tissue collected from participants of the NCRAD Family Study, as well as the NIA Genetics Initiative/NIA‐LOAD Family Based Study (FBS). Approved researchers can obtain tissue from NCRAD, and can also obtain access to genetic data for select subjects from the National Institute on Aging Genetics of Alzheimer's Disease Data Storage Site (NIAGADS). Results: The NCRAD Family Study brain tissue collection includes specimens from 249 subjects from 180 families. 65% of participants were female, the average age of death was 81.4 years, with an average age of dementia onset of 70.18 years for those with reported data. 199 subjects had confirmed or probable AD. 14 subjects had known pathogenic AD mutations in PS1, APP, MAPT, or PGRN . Currently, 186 subjects have been sent for RNA‐sequencing, 123 have GWAS available through NIAGADS, and 71 have sequencing available through NIAGADS. NCRAD has sent DNA from an additional 125 subjects for GWAS and 170 for whole exome sequencing, which will be made available through NIAGADS. The NIA‐LOAD FBS Study includes specimens from 87 subjects from 66 families. 57% of participants were female, the average age of death was 82.9 years, with an average age of dementia onset of 73.5 years. 81 subjects had definite or probable AD. 84 subjects have GWAS data, and 66 subjects have sequencing available through NIAGADS. Subjects from both studies have autopsy data available, including Braak stage, CERAD category, and Reagan category. Conclusion: The brain tissue and clinical information from both these studies are valuable resources for the AD research community, particularly as they are augmented by a growing collection of genetic data. NCRAD strongly encourages researchers to leverage these valuable resources to advance the state of knowledge regarding AD research and therapeutic development.